« Tu jactes kaliarda ? » : la traduction d’un sociolecte LGBTQI+ de la Grèce du XXe siècle, dans Le Cycle de la mort de Thomas Korovinis - Clara Nizzoli (Glad!)
This article develops the characteristics of kaliarda, a Greek LGBTQI+ sociolect, and the issues raised by its translation, and more specifically in the French translation of the novel Le Cycle de la mort by Thomas Korovinis.